DAKWAH DAN PEMBAHARUAN PEMAHAMAN ISLAM - Akhirudin, Akhirudin (Kopertais Wilayah I DKI Jakarta dan Banten, 2018)
Change is the intrinsic nature of society. There is no society without change. He departed the change of mind of the human being who became members of the society. The development of science and technology has spurred the changes. Such changes also suggest changing the religious understanding. In assessing the various changes should da'wah make efforts to renew the understanding of Islam. With Da'wah and Renewal of Understanding of Islam discussed what steps taken by a da'i in the face of the change. In this connection a preacher should really understand the essence of Islamic teachings from the main source of the Qur'an and Sunnah Sahihah and then understand adequately the developments that occur due to the advance of modern science and technology. From these two forms of understanding da'i must be able to provide answers to the needs of the mad'u community who thirst for explanation when they face new problems in daily life that must get a reference from the Qur'an and Sunnah.